PKM PELATIHAN E-COMMERCE BAGI WARGA BELAJAR PKBM 11 MANGGARAI DI MASA PANDEMI COVID 19 - Yunita Indriany; Nika Sintesa (JURNAL ABDIMAS PLJ, 2022)
E-commerce is an activity of distributing, selling, purchasing, marketing products (goods and services), by utilizing the internet network. Even though consumers and sellers do not meet face-to-face, transactions continue to run smoothly. In other words, e-commerce offers convenience in shopping online. Since the Covid-19 Pandemic, the level of internet use in Indonesia has been increasing. This pandemic condition forces or requires people to work from home, and nowadays it is common for us to hear about Work From Home (WFH) or study online. All activities carried out, the majority use the internet, both for personal needs (social media), financial transactions, and even used for face-to-face meetings through cyberspace (webinar or zoom meet or google meet and so on). This community service activity in the form of E-Commerce Training aims to provide knowledge and skills on how to use E-Commerce for electronic commerce to residents learning Community Learning Activity Center (PKBM) Negeri 11 Manggarai as an effective and efficient means of selling/promoting products, as well as encouraging citizens learn to use E-Commerce as a means for business opportunities and business development. The method or method used in carrying out community service activities is to use the online method which is divided into three stages, namely: First, Material Presentation in the form of Theory, Second, Simulation Method. Commerce and the use of smartphones, the three methods of discussion or question and answer between the material filler and the training participants. The participants in this training activity are lecturers from the Jakarta LP3I Polytechnic lecturer. This community service activity will be held on Friday, March 5, 2021, at 13.00-15.00 WIB. This activity went well and was attended by 20 Citizens Learn PKBM Negeri 11 ManggaraiKeywords: E-commerce, Marketing, Internet